2017
DOI: 10.1007/s00128-017-2263-7
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Solvent Terminated Dispersive Liquid–Liquid Microextraction of Copper Ions in Water and Food Samples Using Artificial Neural Networks Coupled Bees Algorithm

Abstract: A multivariate method based on solvent terminated dispersive liquid-liquid microextraction was developed for the determination of Cu ions in aqueous samples. In the proposed approach, di-2-ethylhexylphosphoric acid, xylene and acetone were used as chelating agent, dispersive and extraction solvents, respectively. The effects of various factors on the extraction efficiency such as extraction and dispersive solvent volumes, salt addition and pH were studied using central composite design (CCD) and artificial neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Vicia faba (V. faba) beans have long been used in a number of countries as a traditional food because of its nutritional value and rich content of carbohydrates, fatty acids, proteins, vitamins, and minerals (Inci and Toker, 2011). However, the seed of V. faba bean is very hard and requires prolonged soaking and cooking times for ripening (Farajvand et al, 2018). To accelerate the cooking process and reduce the cost of cooking, some chefs use additives such as citric acid, sodium bicarbonate, and ethylenediaminetetraacetic acid (EDTA) (Lamas et al, 2014; Lanigan and Yamarik, 2002) where the latter was found to decrease the degree of starch gelatinization of black beans ( Phaseolus vulgaris L. ) (Mubaiwa et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Vicia faba (V. faba) beans have long been used in a number of countries as a traditional food because of its nutritional value and rich content of carbohydrates, fatty acids, proteins, vitamins, and minerals (Inci and Toker, 2011). However, the seed of V. faba bean is very hard and requires prolonged soaking and cooking times for ripening (Farajvand et al, 2018). To accelerate the cooking process and reduce the cost of cooking, some chefs use additives such as citric acid, sodium bicarbonate, and ethylenediaminetetraacetic acid (EDTA) (Lamas et al, 2014; Lanigan and Yamarik, 2002) where the latter was found to decrease the degree of starch gelatinization of black beans ( Phaseolus vulgaris L. ) (Mubaiwa et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This review paper attempts to ascertain the criteria that enable the BA to be a workable approach with added value; the algorithm can then be applied to solve the forest transportation planning problem, particularly in Malaysia. Several previous studies such as those of Pham et al (2006), Pham et al (2007), Alfi et al (2011), Abdel Hamid et al (2013) Luo et al (2014 and Farajvand et al (2018), suggest that the BA is capable of yielding accurate results within a short period of time (number of iterations decreased); this can be a good reason to test this algorithm in solving the forest transportation planning problem. The idea comes from the experiment of solving the least-cost transportation problem conducted by Alzaqebah et al (2018) and Szeto et al (2015), who attempted to plan a transportation network by minimizing the cost while taking into account several constraints.…”
Section: Summary Overviewmentioning
confidence: 84%
“…The health risk index of heavy metals was calculated as a percentage of its safety limit. The safety limits were as follows: for Cd, the EFSA panel on contaminants in the food chain designates a PTWI of 2·5 µg/kg (32) ; for Pb, the JECFA reports a PTWI equal to 3·5 µg/kg (33) ; for Zn, the Scientific Committee on Food indicates a tolerable upper limit of 7 mg/d (34) ; for Al, European Union commission limit of 2 mg/kg (35) (PTDI); for Mn, Codex Alimentarius Commission standard limit of 2·5 mg/kg PTWI (36) ; for Co, maximum tolerable daily intake limit of 100 µg/kg bw (37) ; for Cu, PTWI of 3·5 mg/kg (38) ; for As, PTWI limit of 0·015 mg/kg (21) ; for S e, Sn and Hg, PTWI limits of 66 µg/kg, 0·6 mg/kg and 0·4 µg/kg, respectively (38,39) .…”
Section: Methodsmentioning
confidence: 99%